Helicobacter pylori vacA, cagA and iceA genotypes in dyspeptic patients from southwestern region, Saudi Arabia: distribution and association with clinical outcomes and histopathological changes - Mohammed Akeel; Atef Shehata; Ahmed Elhafey; Erwa Elmakki; Thanaa Aboshouk; Hussein Ageely; Mohammed Mahfouz (BMC Gastroenterology, 2019)
Abstract Background The aim of this study was to identify the common H. pylori virulence genes among dyspeptic Southwestern Saudi patients and their association with clinical outcomes and histopathological findings to help practitioners and researchers in the region for better management of infections caused by such bacteria. Methods Four hundred two gastric biopsy specimens were analyzed using histopathological examination and real time-PCR. The positive 187 specimens by RT-PCR were genotyped using PCR targeting cagA, vacA and iceA genes. Results One hundred twenty-eight gastric biopsy specimens were positive in genotyping PCRs. The cagA, vacA, iceA1 and iceA2 genes were detected in rates of 49.2% (63/128), 100%(128/128), 42.2% (54/128), 32.8% (42/128), respectively. The vacA s1as1bm2 subtype was the highest 23.4% (30/128), followed by m2 and s1a1b subtypes which were equally detected [16.4% (21/128) for each]. The iceA genes were significantly associated with gastritis and gastric ulcer. Overall, vacA genotypes were significantly associated with gastritis, gastric and duodenal ulcers. The vacA subtypes: s1as1bm2, s1a1b and s2 m2 showed chronic active gastritis in percentages of 90.0, 81, and 84.2%, respectively. All vacA mixed genotypes showed chronic active gastritis. Conclusions H. pylori virulence genes are highly prevalent and diverse among patients with dyspepsia in Southwestern region of Saudi Arabia. The iceA genes and the different vacA subtypes are significantly associated with the clinical outcomes and histopathological changes especially chronic active gastritis.